Autoimmune-Mediated Retinopathy in CXCR5-Deficient Mice as the Result of Age-Related Macular Degeneration Associated Proteins Accumulation - Lennikov, Anton; Saddala, Madhu Sudhana; Mukwaya, Anthony; Tang, Shibo; Huang, Hu (Frontiers in Immunology, 2019)
Previous research has shown that CXCR5-/- mice develop retinal degeneration (RD) with age, a characteristic related to age macular degeneration (AMD). RD in these mice is not well understood, and in this study, we sought to characterize further the RD phenotype and to gain mechanistic insights into the function of CXCR5 in the retina. CXCR5-/- and WT control mice were used. Fundus images demonstrated a significant (p<0.001) increase of hypo-pigmented spots in the retina of aged CXCR5-/- mice compared with WT control mice. PAS staining indicated localization of deposits in the sub-retinal pigment epithelia (RPE) layer. AMD-associated proteins Cryab, amyloid beta, and C3d were detected within the RPE/sub-RPE tissues by immunofluorescence (IF). In addition, western blot analysis of COX-2, Arg1, and VEGF-a revealed an increase in the signaling of these molecules within the RPE/choroid complex. Transmission electron microscopy (TEM) indicated a drusen-like structure of sub-RPE deposits with an accumulation of vacuolated cellular debris. Loss of photoreceptors was detected by peanut lectin staining and was corroborated by a reduction in MAP2 signaling. Loss of blood-retinal barrier integrity was demonstrated by a reduction of ZO-1 expression. Inflammatory cells were detected in the sub-RPE space, with an increase in IBA-1 positive microglia cells on the surface of the RPE. Mass spectrometry analysis of CXCR5-/- mouse RPE/choroid proteins extracts, separated by SDS-page and incubated with autologous serum, identified autoantibodies against AMD-associated proteins: Cryaa, Cryab, and Anxa2. In vitro evaluations in BV-2 cell culture indicated a significant increase in production of Arg-1 (p<0.001) and COX-2 (p<0.01) in the presence of anti-CXCR5 antibody when compared with Igg-treated control BV-2 cells stimulated with IL-4 and TNFα/IFNγ, respectively. Anti-CXCR5 antibody treatment without stimulating agents did not affect Arg-1 and COX-2 expression; this suggests that CXCR5 may have a regulatory role in microglia cells activation. These results indicate that with age, CXCR5-/- mice develop RD characterized by microglia dysfunction, increased production of CXCL13 in the RPE progressive photoreceptor, neuronal loss, and sub-RPE deposition of cellular debris, resulting in the production of immunogenic proteins and autoimmune-mediated RD.